The added value of three-dimensional transthoracic echocardiography in mitral annular disjunction: a case report - Papadopoulos, Konstantinos; Ikonomidis, Ignatios; Vannan, Mani A. (Frontiers in Cardiovascular Medicine, 2024)
Background Mitral annular disjunction (MAD) refers to the arrhythmic mitral valve prolapse (MVP) syndrome associated with ventricular arrhythmias and sudden cardiac death. Although the pathophysiology of this disease is still under investigation, specific imaging criteria that establish the diagnosis have been recognized. In this article, we demonstrate most of these criteria using three-dimensional transthoracic echocardiography (3D-TTE) and provide added value in the management of MAD syndrome. Case presentation A 50-year-old male patient with recent syncope and a history of mitral regurgitation (MR) and MAD was admitted to our clinic for further investigation. According to our protocol, the patient underwent a complete 3D-TTE, laboratory blood exams, and 24 h ambulatory electrocardiogram (ECG). Our investigation confirmed the presence of MAD syndrome with bileaflet prolapse, severe MR, and non-sustained ventricular tachycardia, necessitating an implantable cardioverter defibrillator (ICD) and surgical mitral valve repair. The 3D-TTE analysis of the mitral valve demonstrated mitral annular systolic expansion and systolic flattening of the saddle-shaped annulus and quantified the extent of the disjunction arc. Additionally, four-dimensional (4D) strain analysis of the left ventricle revealed the presence of fibrosis of the posteromedial papillary muscle and basal inferolateral wall, which are variables that are required for the diagnosis and therapeutic management of MAD syndrome. Conclusions 3D-TTE and 4D strain offer valuable insights for diagnosing and managing patients with MAD syndrome. This method seems to correlate well with the other imaging modalities and could be included in the management protocol of MAD syndrome.